2011
DOI: 10.1158/1535-7163.mct-11-0072
|View full text |Cite
|
Sign up to set email alerts
|

B7-H3 Silencing Increases Paclitaxel Sensitivity by Abrogating Jak2/Stat3 Phosphorylation

Abstract: In many types of cancer, the expression of the immunoregulatory protein B7-H3 has been associated with poor prognosis. Previously, we observed a link between B7-H3 and tumor cell migration and invasion, and in present work we have investigated the role of B7-H3 in chemoresistance in breast cancer. We observed that silencing of B7-H3, via stable shRNA or transient siRNA transfection, increased the sensitivity of multiple human breast cancer cell lines to paclitaxel as a result of enhanced drug-induced apoptosis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
115
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 133 publications
(125 citation statements)
references
References 41 publications
8
115
0
2
Order By: Relevance
“…The growth of established B7-H3 knockdown Maver and Z138 xenografts slowed down compared with their NC groups by 59.1 and 65.0% at the end of observation, respectively. The similar growth inhibition of B7-H3-knockdown xenografts in glioma (22), breast cancer (26) and pancreatic cancer (23) has been observed in other reseach. Furthermore, we found that the expressions of Ki-67 and PCNA were significantly decreased in the B7-H3 silenced MCL xenografts.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The growth of established B7-H3 knockdown Maver and Z138 xenografts slowed down compared with their NC groups by 59.1 and 65.0% at the end of observation, respectively. The similar growth inhibition of B7-H3-knockdown xenografts in glioma (22), breast cancer (26) and pancreatic cancer (23) has been observed in other reseach. Furthermore, we found that the expressions of Ki-67 and PCNA were significantly decreased in the B7-H3 silenced MCL xenografts.…”
Section: Discussionsupporting
confidence: 81%
“…The synergistic cell apoptotic effects in Maver and Z138 cells induced by R and Ben were promoted by B7-H3 knockdown in a time-dependent manner. It indicates that B7-H3 knockdown enhances drug-induced cytotoxicity and apoptosis, and a similar conclusion was drawn in B7-H3 silenced breast cancer cells treated with paclitaxel (26). Furthermore, we detected the activity of caspase-3 in Maver and Z138 cells incubated with R and/or Ben for 24 h, which is the mitochondrial downstream effector caspase in apoptosis signaling cascades.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The JAK2/STAT3 signaling pathway is commonly associated with the emergence of apoptosis resistance in cancer cells, thus representing a potential target for anticancer therapy (26,27). The data in the current study revealed that MUC1 overexpression significantly enhanced the phosphorylation of JAK2 and STAT3 in irradiated HCC cells.…”
Section: Discussionsupporting
confidence: 50%
“…We supposed that this type of molecules may be more closely related to resistance to a specific type of drug but not to the multidrug resistance. Secondly, because of the complexity of non-glycopeptide sample and the undersampling of MS, glycoproteins, such as B7-H3 which was reported to be associated with resistance to paclitaxel in breast cancer cells, can be identified with glycopeptides, but the non-glycopeptide information of them cannot be collected [41]. Therefore we did not subject them for further analysis, either.…”
Section: Discussionmentioning
confidence: 99%